“EFFECTIVE COMMUNICATION FOR BUSINESS TRANSFORMATION” WORKSHOP FOR ENTREPRENEURS - Prathivi, Maria Dini Gilang; Dewobroto, Wisnu Sakti; Lumoring, Jessie (LP2M STP Mataram, 2024)
Through active collaboration between the Entrepreneur Hub Ministry of Cooperation and Small and Medium-Sized Businesses, business owners, and Japri Kreatif as the speaker, a participatory approach was taken to identify the primary business communication needs and develop local, context-appropriate solutions in the Bandung region. Workshops and group discussions are used to provide workshop participants with knowledge about improving communication skills to help their business reach its goals.